A molecular epidemiological study of methicillin‐resistant Staphylococci environmental contamination in railway stations and coach stations in Guangzhou of China. (February 2017) - Lin, J.L.; Peng, Y.; Ou, Q.T.; Lin, D.X.; Li, Y.; Ye, X.H.; Zhou, J.L.; Yao, Z.J.
Abstract: Methicillin‐resistant Staphylococcus aureus (MRSA) has caused a series of public health problems since it was first found in 1961. However, there are few research studies on the MRSA environmental contamination in railway stations and coach stations. Therefore, the aim of this study was to determine MRSA environmental contamination in public transport stations. Between December 2013 and January 2014, 380 surface samples from three railway stations (180) and four coach stations (200) in Guangzhou were collected to isolate and determine the prevalence and characteristics of Staphylococci strains. 39·21% of all samples were Staphylococci isolates, 1·58% of Staphylococci isolates were MRSA isolates, and 6·05% were methicillin‐susceptible S. aureus . The proportion of multidrug resistant among 149 Staphylococci isolates was 75·84%. None of MRSA isolates was identified with the Panton‐Valentine Leukocidin ( PVL ) genes, and one of them was identified with the qac gene. Four MRSA isolates were Staphylococcal Cassette Chromosome mec IVa, and the other two were nontypeable. Staphylococcus aureus isolates were classified into several sequence types (STs), and STs showed possible cross‐transmissions of isolates from various sources. Methicillin‐resistant Staphylococci contamination prevalence was high, and the environment of stations may be the vectors transmitting the Staphylococci to passengers. Significance and Impact of the Study: This is the first study to comprehensively report the prevalence, antibiotic resistance, and molecular characteristics of contamination of Staphylococci isolates in railway stations and coach stations of China. It will have great public health implications on infection control in community settings because of the serious hazard of Staphylococci, especially methicillin‐resistant Staphylococci . Our findings have provided evidence for relevant departments to reduce the contamination of Staphylococci in environment of public transport stations. Abstract : Significance and Impact of the Study: This is the first study to comprehensively report the prevalence, antibiotic resistance, and molecular characteristics of contamination of Staphylococci isolates in railway stations and coach stations of China. It will have great public health implications on infection control in community settings because of the serious hazard of Staphylococci, especially methicillin‐resistant Staphylococci . Our findings have provided evidence for relevant departments to reduce the contamination of Staphylococci in environment of public transport stations.